Clinical comparison of analgesic efficacy of addition of injection dexamethasone 8mg to 20ml 0.5% levobupivacaine in ultrasonography assisted supraclavicular brachial plexus block - Chetali Das; Rajni Mathur; Srishti Kukreja (Journal of Applied Pharmaceutical Research, 2022)
Background: Ultrasonography-assisted supraclavicular block is an efficacious and practical method and allows us to use a lower volume of local anesthetic in compactly arranged brachial plexus. The study envisioned evaluating the analgesic and anesthetic effects of Inj. dexamethasone (8mg) as an adjuvant to 0.5% levobupivacaine to determine the time for first rescue analgesia and number of rescue analgesics needed in 24 hours duration in brachial plexus blockade in adult patients listed for upper limb surgeries. Results: This prospective randomized double-blind interventional study was carried out in ASAI and II, aged 20 to 55 years. In group A (n=30) Inj. Levobupivacaine 20ml and Inj. Normal saline 2ml was given. In group B (n=30) Inj. Levobupivacaine 20ml and Inj. Dexamethasone 2ml was given. The time for the demand of the first rescue analgesia was 431.50 ± 46.15 minutes in group A and 749.38 ± 62.41 minutes in group B, with a p-value < 0.001. The demand for rescue analgesics was more in Group A in contrast to Group B. Conclusion: We deduce with our study, with the addition of dexamethasone, the time for rescue analgesia is prolonged, and the number of rescue analgesic demands is reduced, with a faster onset and extended duration of both sensory and motor block.